eCM 2002
DOI: 10.22203/ecm.v004a05
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of moderately differentiated osteoblast-like cells cultured in contact with bioactive glasses

Abstract: Bioactive glasses have been shown to stimulate osteogenesis both in vivo and in vitro. However, the molecular mechanisms underlying this process are still poorly understood. In this study, we have investigated the behaviour of osteoblast-like cells (MG63), cultured in the presence of bioglass particles. Three types of granules were used: 45S5 ® bioactive glass, 45S5 ® granules preincubated in tris buffer and 60S non-reactive glass, used as control. Phase contrast microscopy permitted step-by-step visualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…A positive effect of bioactive glasses on attachment, proliferation, differentiation and mineralisation of bone cells, compared to non-reactive surfaces has been demonstrated in vitro [25], but the knowledge about the cellular and molecular events underlying is scarce [26]. In our study, both bioactive materials allow healing of critical diaphyseal bone defects in rabbits.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A positive effect of bioactive glasses on attachment, proliferation, differentiation and mineralisation of bone cells, compared to non-reactive surfaces has been demonstrated in vitro [25], but the knowledge about the cellular and molecular events underlying is scarce [26]. In our study, both bioactive materials allow healing of critical diaphyseal bone defects in rabbits.…”
Section: Discussionmentioning
confidence: 62%
“…Results indicate that there are considerable differences in healing potential between the control group and the groups that received cylinders of both types, showing an adequate viability of receiver bone, with absence of inflammatory response around implants as evidence of an adequate in vivo bioactivity [1]. Some bioactive glass compositions (o55 mol% of SiO 2 ) exhibit a high bioactive index and osteoconductivity, and are able to induce osteoproduction by stimulating the proliferation of osteoprogenitor cells [26]. Both tested materials showed osseointegration evidences, and bone growth over its surfaces and subsequent remodelling attempts include cylinders in a new-formed bone diaphysis.…”
Section: Discussionmentioning
confidence: 98%
“…A number of previous studies have shown that certain bioactive glasses can promote proliferation and differentiation of osteoblasts in vitro [4,[6][7][8]19,20]. However, to our knowledge, this is the first report concerning the ability of bioactive glasses to promote differentiation and matrix mineralization in a chondrocyte cell culture system.…”
Section: Discussionmentioning
confidence: 74%
“…MG63 cells do not calcify their extracellular matrix under the culture conditions that we used [24,25]. Osteoblasts and precursor cells can be induced to mineralize by treating them with osteogenic media containing combinations of beta-glycerophosphate, ascorbic acid and dexamethasone [2628], but addition of these factors was an additional variable that had potential to obscure the specific roles of each Wnt protein in osteoblast differentiation.…”
Section: Methodsmentioning
confidence: 99%